2012
DOI: 10.1101/gr.139568.112
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide search for novel human uORFs and N-terminal protein extensions using ribosomal footprinting

Abstract: So far, the annotation of translation initiation sites (TISs) has been based mostly upon bioinformatics rather than experimental evidence. We adapted ribosomal footprinting to puromycin-treated cells to generate a transcriptome-wide map of TISs in a human monocytic cell line. A neural network was trained on the ribosomal footprints observed at previously annotated AUG translation initiation codons (TICs), and used for the ab initio prediction of TISs in 5062 transcripts with sufficient sequence coverage. Funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
187
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(192 citation statements)
references
References 68 publications
3
187
1
1
Order By: Relevance
“…Recent ribosome profiling studies have illustrated that previously uncharacterized uORFs with non-canonical initiation codons are more commonly translated than previously thought (3,4,6). This observation has been followed by the characterization of multiple mechanisms involving bypass of uORFs due to their non-canonical initiation codons that regulate gene-specific translation during cellular stress conditions (4,26,68).…”
Section: Ribosome Bypass and Non-canonical Start Codonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent ribosome profiling studies have illustrated that previously uncharacterized uORFs with non-canonical initiation codons are more commonly translated than previously thought (3,4,6). This observation has been followed by the characterization of multiple mechanisms involving bypass of uORFs due to their non-canonical initiation codons that regulate gene-specific translation during cellular stress conditions (4,26,68).…”
Section: Ribosome Bypass and Non-canonical Start Codonsmentioning
confidence: 99%
“…This finding indicates that those uORFs that are retained throughout species likely maintain functional significance. This idea is emphasized in genome-wide analyses of uORF conservation in which the presence of an uORF and the regulatory nature of uORF(s) is suggested to be conserved throughout species (6,7,(85)(86)(87).…”
Section: Evolutionary Conservation Of Uorf-mediated Translation Mechamentioning
confidence: 99%
“…Prior to the development of Ribo-Seq, translated uORFs with regulatory functions were often identified by mutant screening or evolutionary conservation (Hill and Morris, 1993;Delbecq et al, 1994;Wiese et al, 2004;Imai et al, 2006;Hayden and Jorgensen, 2007). Although Ribo-Seq data have been used in the identification of translated uORFs (Fritsch et al, 2012;Liu et al, 2013;Ingolia et al, 2014), the application of Ribo-Seq data to the identification of ribosome stalling uORFs has not been reported. In this study, we show that some CPuORFs overaccumulate 59-truncated RNA ends with a signature of stacked ribosomes (Figure 2A).…”
Section: Investigation Of Regulatory Uorfs Using the Rna Degradomementioning
confidence: 99%
“…Recently, a global approach to discover uORF and NH 2 -terminally extended proteins using ribosomal footprinting in a monocytic cell line (THP-1) showed that about half of the annotated coding sequences have uORF that might have an effect on their expression (18). The same technique was employed to assess the effects of oxidative stress on translation in yeast (21).…”
Section: Discussionmentioning
confidence: 99%